2017
DOI: 10.1002/adsc.201700744
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Catalyzed Formal [3+2] Cycloaddition of Donor‐Acceptor Cyclopropanes and 1‐Azadienes: Synthesis of Imine Functionalized Cyclopentanes and Pyrrolidine Derivatives

Abstract: Lewis acid catalyzed formal [3 + 2] cycloadditions of 1-azadienes with donor acceptor cyclopropanes to synthesize varieties of imine functionalized cyclopentanes and pyrrolidine derivatives in moderate to high yield have been developed. Moreover, pharmaceutically relevant azabicyclo[3.2.1] octane, bearing two all-carbon quaternary stereogenic centers at the bridgehead positions, has been synthesized by nosyl group deprotection and intramolecular amidation of imine functionalized cyclopentane derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 43 publications
0
19
0
2
Order By: Relevance
“…Previously, our group has observed that 10 or 20 mol% of MgI 2 is a fruitful catalyst for the ring opening cycloaddition reaction of DACs with other strained rings such as epoxides and aziridines and also with other substrates (1‐azadiene, oxathianes, thiazines, etc.) ,. Based on previous experiences, we started the cycloaddition with 10 mol% of MgI 2 which furnished 58% yield of 3 aa (Table , entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our group has observed that 10 or 20 mol% of MgI 2 is a fruitful catalyst for the ring opening cycloaddition reaction of DACs with other strained rings such as epoxides and aziridines and also with other substrates (1‐azadiene, oxathianes, thiazines, etc.) ,. Based on previous experiences, we started the cycloaddition with 10 mol% of MgI 2 which furnished 58% yield of 3 aa (Table , entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, [4+n] cycloaddition reactions of azadienes with DACs are not reported yet in the literature. We have recently reported a Lewis acid catalyzed formal [3+2]‐cycloaddition of DACs with azadienes, wherein cyclopropanes act as “classical” 1,3‐zwitterion to afford N ‐tosyl, or nosyl imine functionalized cyclopentanes and pyrrolidine derivatives . Encouraged by these results, we took an interest to explore the reactivity of DACs with chalconimine.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these previous findings, we were curious to find out whether it is possible to react D–A cyclopropanes 1 with the 1,3‐dithiane‐containing α,β‐unsaturated ketone 2 in a (3+2)‐cycloaddition . It should be possible to convert the emerging dithiaspiro compounds 3 to the corresponding 1,3‐diketones using NIS, ultimately leading to the formal insertion of a monosubstituted ketene into a D–A cyclopropane (Scheme b).…”
Section: Methodsmentioning
confidence: 99%
“…[24] Similarly, only (3 + 2)-cycloadducts were obtained by other authors in reactions of diverse D-A cyclopropanes with a variety of 1,3-dienes. [25] Furans themselves are often used as 4p-component in both Diels-Alder reactions [26] and (4 + 3)-cycloadditions with various 1,3-dipoles. [27] However, furan derivatives can also react as 2p-components affording products of (2 + 1)-, [3,28] (2 + 2)-, [29] (2 + 3)- [30] and (2 + 4)-cycloadditions.…”
Section: (3 + 2)-cycloaddition To 13-dienesmentioning
confidence: 99%